DUAL LEADERSHIP: CHIEF EXECUTIVE OFFICER AND CHIEF FINANCIAL OFFICER - (:unkn) unknown (European University's Institute for the Research of Economic and Social Problems of Globalization, 2018)
The role of administrators on successful operations of businesses management is very high. Ability of management’s, attitudes and behaviors, and perspective on financial events are closely related to the success of the business. The highest-level decision body in the management of the company is the CEO. He is responsible for the success and failure of enterprise. A failed CEO can cause the business to fall into financial difficulty. In that case the manager’s financial ability, risk and return balance and management of assets and resources are become importance. In order to perform these tasks, it is necessary to have CFO as senior manager. For this reason, it is developing a dual leadership model to strengthen the financial organization structure of the enterprises. CEO and CFO in the model are at the top of the organizational chart. CFO is responsible for accounting and finance units; CEO is for other units. Because the CEO and CFO in the model are at the same level, they need to make decisions together. If the decisions of the CEO and CFO conflict Executive board resolves the problem. In the model, a functional organization chart is prepared, and the authority and duties of CEO and CFO are defined. In this study, the finance-oriented management of enterprises is strengthened, literature is gained a new model which name “dual leadership: CEO and CFO”.